Analisis Lingkungan Perusahaan dan Strategi Perusahaan serta Dampaknya pada Kinerja UMK Batik - Soekardan, Dadan; Juju, Undang (Jurnal Trikonomika, 2012)
Trusmi Batik Center of Cirebon is one of Batik producer areas that has been established for many years,but as a matter of fact the number of Batik producer has been decreased and this cause they can not meet the needs of market demand and donât have integrated competitive strategy among the members of the Batik Center itself hence they donât have power for sustainable competitive advantage. The research findings indicated that the Batik producer problem nowadays is that the increasing price of raw material, inefficiency of production technique, related institution program hasnât solve the problem, art and culture that exist in the society, the quality of the raw material supplied, the ability of mediator, and cooperation among the Batik makers.The internal factors that related to the companies environment are: pre-marketing, marketing, post marketing, the lack of capital sources, in adequate capital as well as the lack of efficiency when they encounter lack of capital.The number, skill, and productivity of employees can not support the achievement of the companyâs objective. Based on the external environment analysis as well as UMK internal, that a Cooperation Model of Micro and Small Scale Business that market demand orientated is highly needed.This organization is to build the sustainable competitive ability as well as to enhance the business effectivity in order to increase the batik producers income and batik industries.